Efficacy and Safety of Enteral Erythromycin Estolate in Combination With Intravenous Metoclopramide vs Intravenous Metoclopramide Monotherapy in Mechanically Ventilated Patients With Enteral Feeding Intolerance: A Randomized, Double‐Blind, Controlled Pilot Study. Issue 6 (2nd October 2020) - Charoensareerat, Taniya; Bhurayanontachai, Rungsun; Sitaruno, Sirima; Navasakulpong, Asma; Boonpeng, Apinya; Lerkiatbundit, Sanguan; Pattharachayakul, Sutthiporn
Abstract: Background: In this pilot study, we aimed to determine the efficacy and safety of enteral erythromycin estolate in combination with intravenous metoclopramide compared to intravenous metoclopramide monotherapy in mechanically ventilated patients with enteral feeding intolerance. Methods: This randomized, double‐blind, controlled pilot study included 35 mechanically ventilated patients with feeding intolerance who were randomly assigned to receive 10‐mg metoclopramide intravenously every 6–8 hours in combination with 250‐mg enteral erythromycin estolate (study group) or placebo every 6 hours for 7 days. The primary outcome was an administered‐to‐target energy ratio of ≥80% at 48 hours, indicating a successful feeding. Secondary, prespecified outcomes were daily average gastric residual volume (GRV), total energy intake, administered‐to‐target energy ratio, hospital length of stay, in‐hospital mortality, and 28‐day mortality. Results: The rate of successful feeding was not significantly different between the study and placebo groups (47.1% and 61.1%, respectively; P = .51). The average daily GRV was significantly lower in the study group than in the placebo group (β = 91.58 [95% Wald CI, −164.35 to −18.8]), determined by generalized estimating equation. Other secondary outcomes were comparable, and the incidence of adverse events was not significantly different between the 2 groups. One common complication was cardiac arrhythmia, which was mostly self‐terminated. Conclusion: Although the combination therapy of enteral erythromycin estolate and intravenous metoclopramide reduced GRV, the successful feeding rate and other patient‐specific outcomes did not improve in mechanically ventilated patients with feeding intolerance.